(untitled) (Plant Tissue Culture and Biotechnology, 2014)
This protocol has been developed for somatic embryogenesis in Hedychium spicatum. Simultaneously, a method has also been developed for the production of synthetic seeds by using somatic embryos. Direct somatic embryos were developed on cotyledon explants of zygotic embryos on MS supplemented with high concentration of NAA (20.0 µM). Induction of secondary embryogenesis was best in 2,4-D supplemented medium fortified with activated charcoal. Germination of somatic embryos was enhanced by using GA3. Besides this, round and semi-hard beads of somatic embryos (synthetic seeds) could be produced by using 2% Na-alginate and 100 mM calcium chloride and more than 30% germination of synthetic seeds was achieved in MS. Well acclimated plants produced via somatic embryogenesis and/or synthetic seeds were transferred to field where more than 60% survived. This simple study enabled us to obtain a number of plantlets throughout the year each cycle requiring a short period of time. Besides propagation, this study provided an ex situ method for conservation of this vulnerable Himalayan species. D. O. I.http://dx.doi.org/10.3329/ptcb.v23i2.17506 Plant Tissue Cult. & Biotech. 23(2): 147-155, 2013 (December)